Ice protection systems for wind turbines in cold climate: characteristics, comparisons and analysis. (November 2016) - Fakorede, Oloufemi; Feger, Zoé; Ibrahim, Hussein; Ilinca, Adrian; Perron, Jean; Masson, Christian
Abstract: The impact of icing on wind turbines and energy production in northern regions is a severe problem. Therefore, emphasis on developing ice mitigation systems has become a significant part of the wind energy conversion systems. These systems use various technologies and have different specifications, sometimes with no clear indication of their efficiency. Since the effect of cold climate on wind turbines is complex, not every ice protection system is suitable for a given wind farm. Therefore, the aim of this work is to compare the existing ice mitigation solutions and provide an indication on their efficiency. In this paper, we first review the most recent standards set by experts, and the major issues associated with wind energy in cold climates. Then, we present the ice protection techniques found in the literature, and then highlight the recent research on the optimization of the systems. Finally, we present an analysis of the current market, compare ice protection techniques and systems, based on various criteria, and measure the additional costs generated by ice mitigation.